(3GdeSDhdjI GdGLJeGYjI ddTQcGJ fMh GdJfejI GdeSJOGeIs - (3YGjO YHO Gddg(B, (3GdYUjejs ((3YeGf(B:s (3GdjGRhQj(B,s, 2015)
(3jVe GdeSDhdjI GdGLJeGYjI ddTQcGJ , GdJfejI GdeSJOGeI , GdSjGSGJ GdYGeI ddeSDhdjI GdGLJeGYjI ddTQcGJ , GdTQGcI Hjf GdbWGYjf GdYGe hGdNGUs
Keywords: (3GdJfejI GdeSJOGeIs; (3GdTQcGJs; (3GdTQcGJ(B- (3ELJeGYjGJs; (3GdeSDhdjI GdELJeGYjIs